2022
DOI: 10.1039/d1nr06036h
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying inorganic chirality using liquid crystals

Abstract: We summarize the current progress of amplifying inorganic chirality using liquid crystals. Chiral interactions between inorganic components and liquid crystals, representative applications, and the perspectives of this field are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Different from other chiral soft templates, chiral liquid-crystalline templates are known to show multitudinous advantageous attributes, such as long-range molecular ordering, structural diversity of chiral mesogenic phases, and superior responsiveness to many external stimuli, such as light, temperature, electric field, mechanical force 1,2,77,98 . Importantly, many researchers have demonstrated that using chiral liquid crystals as soft templates can effectively amplify the chirality of nanomaterials and increase the optical asymmetry [148][149][150][151] . In this section, we shall introduce recent endeavors in the development of chiral plasmonic nanomaterials with various thermotropic and lyotropic liquid crystal templates.…”
Section: Liquid Crystal-templated Chiral Plasmonic Nanomaterialsmentioning
confidence: 99%
“…Different from other chiral soft templates, chiral liquid-crystalline templates are known to show multitudinous advantageous attributes, such as long-range molecular ordering, structural diversity of chiral mesogenic phases, and superior responsiveness to many external stimuli, such as light, temperature, electric field, mechanical force 1,2,77,98 . Importantly, many researchers have demonstrated that using chiral liquid crystals as soft templates can effectively amplify the chirality of nanomaterials and increase the optical asymmetry [148][149][150][151] . In this section, we shall introduce recent endeavors in the development of chiral plasmonic nanomaterials with various thermotropic and lyotropic liquid crystal templates.…”
Section: Liquid Crystal-templated Chiral Plasmonic Nanomaterialsmentioning
confidence: 99%
“…[12,[22][23][24][25][26][27] On the basis of different composition, CPL materials are generally grouped into six categories: Polymers, [28][29][30][31][32][33][34][35][36] small organic molecules, [37][38][39] supramolecular assemblies, [23,[40][41][42] liquid crystals, [43][44][45] metal complexes, [46][47][48][49][50] and inorganic materials. [51][52][53] Amongst the categories, CPL materials constructed from polymers have inherent advantages. For instance, biological polymers such as DNA, proteins, and polysaccharides featuring both inherent molecular chirality and helical chirality provide rich chiral sources and elegant architectures for constructing CPL materials.…”
Section: Polymer-based Circularly Polarized Luminescent Materialsmentioning
confidence: 99%
“…Circularly polarized luminescence (CPL), generated by the intrinsic chirality − of luminescent materials, is a lesser-known type of emission and is not easy to replicate without advanced chiral expertise, offering promise in the application of information encryption and anticounterfeiting. , To serve the soaring needs for anticounterfeiting technology, we take a step further to incorporate more information encoding on top of CPL to achieve multilayer optical authentication, using a helical-coassembly strategy to incorporate quantum dots (QDs) and liquid crystals.…”
Section: Introductionmentioning
confidence: 99%